(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The Research examines the complex interactions that exist between India’s political system, global warming regulations, and climate change. It explores the complex aspects of India’s climate change response, examining the political forces at play and the policy proposals that the country has put forth. It also emphasizes how institutions, political players, and public discourse have shaped the course of climate policy while taking into account the variety of interests and priorities that affect how decisions are made. The impacts of global warming on the climate are multifaceted, encompassing both physical changes in Earth’s climate systems and unintended consequences of mitigation efforts. These effects extend beyond the biosphere to human societies and ecosystems, presenting complex challenges. While physical changes include increased storms, droughts, heat waves, and other extreme weather events, mitigation efforts often exacerbate socio-economic disparities, particularly in developing nations. Observations reveal alarming trends such as rising sea levels, glacier loss, and shifts in biodiversity. Additionally, ocean acidification and warming pose threats to marine life and ecosystems. In response, the Indian government has implemented various initiatives, including environmental policies and pollution abatement strategies, to address climate Change Impacts.